GERBERA DISEASES IN THE STATE OF PARANÁ, BRAZIL - FERRONATO, Marlene de Lurdes; LIMA NETO, Vismar da Costa; TOMAZ, Roberto (Scientia Agraria, 2008)
In surveys carried out in nine regions of Paraná State between the 1st semester of 2004 and the 2nd semester of 2006, comprising 15 properties growing cut and potted gerbera (Gerbera jamesonii), nine plant pathogenic agents were identified: eight of fungal and one of bacterial nature (Erysiphe cichoracearum, Pythium sp., Phytophthora sp., Fusarium oxysporum, Cercospora gerberae, Botrytis cinerea, Albugo tragopogonis, Capnodium sp. and Pseudomonas cichorii). The identification of these pathogens, descriptions of symptoms and period of occurrence provides some basic information for future researches on epidemiology and control of gerbera diseases in the Paraná State, Brazil.